KEBIJAKAN PEMERINTAH DAERAH DALAM MENINGKATKAN KUALITAS PELAYANAN PERSAMPAHAN DINAS PENGELOLAAN LINGKUNGAN HIDUP DAN KEINDAHAN KOTA MAKASSAR - Baiq Aprimawati (Jurnal Ilmu Pemerintahan Widya Praja, 2016)
In several cities generally waste management is provided by Jakarta the city cleansing. Community involvement and private parties in dealing with waste in several cities have been done to some typesof activities. Many community sector involved in collecting the garbage in the heap of garbage, whilethe providers are generally manage waste in an elite area where paying ability from the customers isalready quite high. In the conduct of waste service, the government of Makassar will stipulate policiesthe region about waste fees or hygiene.